WANPRESTASI PERJANJIAN RUMAH TOKO DI JALAN SIDOMULYO NOMOR 4 KECAMATAN NANGA PINOH KABUPATEN MELAWI - Stefanus Ngebi (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2021)
In steering a cooperative-work or business affiliation in the field of lease a building, whereas for the case of this research is a house store, it is certainly every single business actor should create rules of the game as outlined in the form of an agreement between the parties covered in order to evade legal problems that occur in the future. The parties must construct an agreement used as a legal base which obeyed by the parties covered. The approach used in this research is a Sociological Juridical Method. The approach is defined as problem analysis through legal research of factual facts in institution concerned or toward the community which covered as problems handled in the research. This research is designed in form of descriptive analysis which identifies the whole systematic object of the research problem. Furthermore, if the agreement that have been agreed upon by the parties concerned are not properly applied, as a consequences one of the parties can prosecute for compensation due to carelessness or it may also clarify in legalterms one of the parties defaults on the lease agreements that have been mutually approved. As result, In the implementation of the rental agreement of rent a house store between a lessor and the lessee on Sido Mulyo avenue, Nanga Pinoh District, Melawi Regency, it is implemented properly with the phases accomplish by the parties as follows: arising fromnegotiationstosigningtheleaseagreement letter and it should be as responsibilities of the all parties in accomplishing it properly as decided on the the agrreement of rent a house store on the sidomulyo avenue, Nanga pinoh district, Melawi regency. Moreover, in each cancellation of the agreement, all the risk of the lease will be as a responsibility of the lessee if it is canceled. Thus, the agreement must be implemented in good trust on the rights and obligations attached for each party. It also the contents of the agreement must be regulated complete with presence of sanctions. If there is negligence in adhering to the contents of the agreement, a legal formal should provide an appropriate settlement. Along with it, the design of the contents of the agreement is accomplished in a meticulous and decisive. Thus, the responsibilities of the parties toward the rights and obligations of each party immediately accomplished.